can anyone solve this
![hots \: question \: i \: n \: minimum \: time \\ hots \: question \: i \: n \: minimum \: time \\](https://tex.z-dn.net/?f=hots+%5C%3A+question+%5C%3A+i+%5C%3A+n+%5C%3A+minimum+%5C%3A+time+%5C%5C+)
Attachments:
![](https://hi-static.z-dn.net/files/d27/aa62ddc9dfad2781dcd97744df8d1c86.jpg)
Answers
Answered by
2
Given pth term = 1/q
That is ap
= a + (p - 1)d
= 1/q aq + (pq - q)d = 1 --- (1)
Similarly, we get ap + (pq - p)d = 1 --- (2)
From (1) and (2),
we get
aq + (pq - q)d = ap + (pq - p)d aq - ap = d[pq - p - pq + q] a(q - p) = d(q - p)
Therefore, a = d
Equation (1) becomes,
dq + pqd - dq = 1 d = 1/pq
Hence a = 1/pq
Consider, Spq = (pq/2)[2a + (pq - 1)d] = (pq/2)[2(1/pq) + (pq - 1)(1/pq)] = (1/2)[2 + pq - 1] = (1/2)[pq + 1]
That is ap
= a + (p - 1)d
= 1/q aq + (pq - q)d = 1 --- (1)
Similarly, we get ap + (pq - p)d = 1 --- (2)
From (1) and (2),
we get
aq + (pq - q)d = ap + (pq - p)d aq - ap = d[pq - p - pq + q] a(q - p) = d(q - p)
Therefore, a = d
Equation (1) becomes,
dq + pqd - dq = 1 d = 1/pq
Hence a = 1/pq
Consider, Spq = (pq/2)[2a + (pq - 1)d] = (pq/2)[2(1/pq) + (pq - 1)(1/pq)] = (1/2)[2 + pq - 1] = (1/2)[pq + 1]
Answered by
1
here is your answer
hope it helps you....
Attachments:
![](https://hi-static.z-dn.net/files/d90/90790aa2c104a0a3a4dc0da144696e75.jpg)
![](https://hi-static.z-dn.net/files/dbc/9a1bf8f7da7f8ccea0632202be8b988a.jpg)
last3daysofsscboard:
I can't understand last from sum of p and q
Similar questions